Earthquakes in the Valmarecchia area (Northern Apennines, Italy) - Zei, Caterina; Ciucciarelli, Cecilia; Tarabusi, Gabriele; Guerra, Cristiano; Ghirotti, Monica; Valensise, Gianluca (Italian journal of engineering geology and environment, 2024)
The Valmarecchia area, located between the Emilia-Romagna and Marche administrative regions, is characterized by numerous landslides and has been affected by earthquakes occurring both outside and inside its territory. As earthquakes are one of the main causes of gravitational phenomena, we investigated the occurrence of earthquake-induced landslides, starting from the events that were reported as felt in any of the Valmarecchia municipalities. We analyzed their magnitude and distance from the area and identified the seismotectonic areas that generated them. We found that more than half of the earthquakes that hit Valmarecchia historically could have generated shaking-induced landslides; and yet, based on the ample documentation stored in online portals, we also found that the number of earthquakes for which there exists historical evidence for such phenomena is very limited. This is likely the result to lack of information on the correlation among earthquakes and landslides, possibly justified by the local historical and geographical context and by the seismotectonic marginality of Valmarecchia, located off the main seismogenic trends of the Italian peninsula. We aim to improve knowledge on Valmarecchia seismicity and to illustrate a methodology for identifying both earthquake-induced effects and the areas that are prone to these phenomena.